Percutaneous balloon angioplasty in central venous stenosis and occlusion in haemodialysis vascular access: comparison of the outcome - Wahed, Haniza (2013)
Central venous occlusive disease is currently increasing in trend, in view of improved health care and lifestyle changes. Central venous occlusive disease requires treatment, especially in hemodialysis patient. Venous hypertension in this disease interfere the hemodialysis access and eventually leading to its dysfunction and access termination. Interventional radiology has emerged in endovascular treatment, playing its important role in treatment of central venous occlusive disease. Surgical intervention has been less favourable in the management of central venous occlusive disease, indirectly reduces the health care burden. The current practice of central venous occlusive disease is an endovascular approach as a frontline. However there is no proper protocol in managing the disease. In this study, success rate in venous stenosis and venous occlusion were compared and the association of degree of stenosis and length of occlusion with success rate has been studied. Hopefully it will help in predicting the patient which is suitable for endovascular management or surgery and contributing in developing a proper management protocol in the future. This is a cross sectional retrospective study of percutaneous angioplasty in the treatment of central venous stenosis and occlusion in Hospital Pulau Pinang for period 21 months from May 2011 to February 2013. The patient’s notes were traced and data were collected on the success rate, complication rate, presence and location of stenosis, degree of stenosis and length of occlusion. Venograms were reviewed in all cases to assess lesion characteristics, pre procedure and post procedure results. Descriptive analysis was used to analyze the demographic data. 71 patients were included into this study of which 42 (59.2%) males and 29 (40.8%) females. Their age ranged from 17 to 86 years old. 21 (29.6%) were Malay, 39 (54.9%) Chinese and 11 (15.5%) are Indian. From total 71 patients, 28 (39.4%) cases are were venous stenosis and 43 (60.6%) cases were venous occlusions. 25 out of 28 cases of venous stenosis were successfully treated with success rate of 89.3%. 19 out of 43 cases of venous occlusion were successfully treated with success rate of 44.2%. There is association between the success rate of procedure and degree of stenosis and length of occlusion. The success rate of percutaneous angioplasty in central venous stenosis is higher (89.3%) compare to total venous occlusion (44.2%) among haemodialysis patient. The degree of stenosis and length of occlusion is significantly associated with the success rate of percutaneous balloon angioplasty.